2012
DOI: 10.1051/alr/2012002
|View full text |Cite
|
Sign up to set email alerts
|

Are sex ratios in wild European sea bass (Dicentrarchus labrax) populations biased?

Abstract: -Sex ratios in farmed European sea bass are highly biased towards males (75 to 95%), which is problematic for aquaculture. In this mini-review, we re-analyse fisheries literature data about sex ratios in wild sea bass from 13 population samples, representing altogether 4889 individuals covering the major part of the distribution range of the species. We find that as a whole, the sex ratio of wild populations is biased towards females (59.4% females, p < 0.001), but that the sex ratio of the younger fish (<30 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
(40 reference statements)
3
23
0
Order By: Relevance
“…Studies in other environments have also shown a strong female bias in various Clupeiformes species (Fialho et al, 2000;Corrêa et al, 2005;Deshmukh et al, 2010). This bias could be explained by ecological factors (Gamble and Zarkower, 2012), environmental conditions, reproductive behavior, or food availability (Vandeputte et al, 2012). High female bias might also represent an adaptive strategy to boost egg numbers, resulting in more offspring being recruited (García-Abad et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other environments have also shown a strong female bias in various Clupeiformes species (Fialho et al, 2000;Corrêa et al, 2005;Deshmukh et al, 2010). This bias could be explained by ecological factors (Gamble and Zarkower, 2012), environmental conditions, reproductive behavior, or food availability (Vandeputte et al, 2012). High female bias might also represent an adaptive strategy to boost egg numbers, resulting in more offspring being recruited (García-Abad et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The sex ratio may vary from the expected 1:1 from species to species, or even in the same population at different times, being influenced by several factors such as adaptation of the population, reproductive behavior, food availability and environmental conditions (Nikolsky, 1963;Emlen and Oring, 1977;Baroiller and D´Cotta, 2001;Brykov et al, 2008;Vandeputte et al, 2012).…”
Section: Sex Ratiomentioning
confidence: 99%
“…The consequences of deforestation on mangrove fauna have not yet been documented in West Africa. The significant role of crabs as a engineer species starts to be recognized, but their ecological answers with respect to human pressures are poorly known compared to other aspects of their life such as diversity, distribution, sex ratio, ecological roles, feeding ecology, plant periodical migrations, physiological adaptations, domestic wastewater effects,… [22,23,24,25,26,27,28,29,30]. So, the aim of this study is to determine the impact of human pressures on mangrove crab biodiversity in Cameroon.…”
Section: Introductionmentioning
confidence: 99%